Suppression of nodulation gene expression in bacteroids of Rhizobium leguminosarum biovar viciae. - Schlaman, H R (1991)
The expression of nod genes of Rhizobium leguminosarum bv. viciae in nodules of Pisum sativum was investigated at both the translational and transcriptional levels. By using immunoblots, it was found that the levels of NodA, NodI, NodE, and NodO proteins were reduced at least 14-fold in bacteriods compared with cultured cells, whereas NodD protein was reduced only 3-fold. Northern (RNA) blot hybridization, RNase protection assays, and in situ RNA hybridization together showed that, except for the nodD transcript, none of the other nod gene transcripts were present in bacteroids. The amount of nodD transcript in bacteroids was reduced only two- to threefold compared with that in cultured cells. Identical results were found with a Rhizobium strain harboring multicopies of nodD and with a strain containing a NodD protein (NodD604) which is activated independently of flavonoids. Furthermore, it was found that mature pea nodules contain inhibitors of induced nod gene transcription but that NodD604 was insensitive to these compounds. In situ RNA hybridization on sections from P. sativum and Vicia hirsuta nodules showed that transcription of inducible nod genes is switched off before the bacteria differentiate into bacteroids. This is unlikely to be due to limiting amounts of NodD, the absence of inducing compounds, or the presence of anti-inducers. The observed switch off of transcription during the development of symbiosis is a general phenomenon and is apparently caused by a yet unknown, negative regulation mechanism.